Análises citogenéticas em espécies de peixes Gymnotus (Pisces, Gymnotidae), coletadas no Córrego Fundo, Alfenas, Minas Gerais. - Lacerda, Maria Conceição Vieira (2005)
Three sympatric species of Gymnotus from the Fundo stream a small tributary of the Sapucaí river Minas Gerais State Brazil were studied in relation to their karyology Gymnotus sylvius presented 2n = 40 chromosomes (36 m/sm + 4 st/a) Gymnotus sp presented 2n = 50 (44 m/sm + 6 st/a) and Gymnotus paraguensis had 2n = 54 (50 m/sm + 4 st/a) C-banding demonstrated positively stained heterochromatic blocks in the centromeric position of few chromosomes on G sylvius and in the centromeric region of all chromosomes on G paraguensis samples The nucleolus organizer region (NOR) was located on the short arm of one st chromosome pair in G sylvius and Gymnotus sp and in the interstitial position on the short arm of the pair number one and below the centromere on a third chromosome on G paraguensis The cytogenetic data obtained indicate that Gymnotus sp represent a new Gymnotus species with a karyotypic constitution never observed on other species from this genus Some aspects related to the chromosome diversification of these Gymnotus are discussed